Visual Requirements and its Relation with Road Traffic Accident in Saudi Arabia - Rayan Nasser Almutairi, Mohammad Shakil Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Driving is the act of operating and moving vehicles for which it is critical for drivers to recognize road signs, pedestrians, and animals when on the road. In Saudi Arabia it is estimated that there are over 1 million car accidents per year in which almost 80% are due to vision issues. The aim of the study is to assess the need of visual test and its relation with RTA. Material and methods: This study has followed cross sectional study design conducted among driving license holders aged (17-60) who could be both the resident and non-resident of Saudi Arabia. A structured questionnaire was used to collect data for 550 calculated samples using the online platform. The data was analyzed using excel-13 and SPSS-21. T-test was used to compare vision with correction and number of accidents; vision without correction and number of accidents whereas ANOVA and Post-Hoc test was used to compare the number of accidents among different age groups. Results: This study involves the information collection among 550 respondents who had received the driving license under the Government of Saudi Arabia. Among the respondents, majority (33%) of them were from the age group 17 to 27. The prevalence of vision problem among respondents was 45% in which 72% had their visual correction. All the respondents who did not had visual correction has faced any sort of road traffic accident as the reverberation of denial towards need of visual correction. The study also performed comparative analysis to see the various relations among the driver’s visual status and the road traffic accidents, were more number of accidents were recorded among respondents around 17-27 years of age. The study also reflected that there was no statistically significant difference in mean number of accidents between any other age group. Conclusion: Saudi Arabia has one of the highest accidents rate in the world by over 1 million accidents in 2016. This study has significantly highlighted the risk age group and people’s denial towards visual correction leading to increase in rate of road traffic accident. So there is need of strictly implementing compulsory vision checkup with medical professional and revised standard visual requirement for obtaining driving license.